Cu3V2O8 Nanoparticles as Intercalation‐Type Anode Material for Lithium‐Ion Batteries. Issue 32 (30th June 2016) - Li, Malin; Gao, Yu; Chen, Nan; Meng, Xing; Wang, Chunzhong; Zhang, Yaoqing; Zhang, Dong; Wei, Yingjin; Du, Fei; Chen, Gang
Abstract: Cu3 V2 O8 nanoparticles with particle sizes of 40–50 nm have been prepared by the co‐precipitation method. The Cu3 V2 O8 electrode delivers a discharge capacity of 462 mA h g −1 for the first 10 cycles and then the specific capacity, surprisingly, increases to 773 mA h g −1 after 50 cycles, possibly as a result of extra lithium interfacial storage through the reversible formation/decomposition of a solid electrolyte interface (SEI) film. In addition, the electrode shows good rate capability with discharge capacities of 218 mA h g −1 under current densities of 1000 mA g −1 . Moreover, the lithium storage mechanism for Cu3 V2 O8 nanoparticles is explained on the basis of ex situ X‐ray diffraction data and high‐resolution transmission electron microscopy analyses at different charge/discharge depths. It was evidenced that Cu3 V2 O8 decomposes into copper metal and Li3 VO4 on being initially discharged to 0.01 V, and the Li3 VO4 is then likely to act as the host for lithium ions in subsequent cycles by means of the intercalation mechanism. Such an "in situ" compositing phenomenon during the electrochemical processes is novel and provides a very useful insight into the design of new anode materials for application in lithium‐ion batteries. Abstract : Cu3 V2 O8 electrodes : Cu3 V2 O8 nanoparticles, prepared as an anode material, deliver a discharge capacity of 462 mA h g −1 for the first 10 cycles that increases to 773 mA h g −1 after 50 cycles, possibly as a result of extra lithium storage. The electrode also shows good rate capability. The Cu3 V2 O8 decomposes into copper and Li3 VO4 on being initially discharged to 0.01 V, and the Li3 VO4 then acts as host for lithium ions in subsequent cycles through an intercalation mechanism (see figure) with the copper enhancing the conductivity.